Dusty Viscous Flow Through a Cylinder of Rectangular Cross Section Under Time Dependent Pressure Gradient - Rukmangadachari, E. (Defence Science Journal, 2014)
Unsteady laminar flow of a dusty, viscous, incompressible fluid through a cylindrical tube of rectangular cross-section is studied when the pressure gradient varies (i) exponentially and (ii) harmonically w.r.t. time. The velocity fields for the fluid and the dust particles have been obtained. Results in limiting cases are derived. Flux and drag have been calculated. Flow through a tube of square section and flow between parallel plates have been obtained as special cases.